Occurrence of cereal viruses on wheat in Tekirdag, Turkey - Köklü, Gassan (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2004)
AbstractA survey for detection of barley yellow dwarf luteoviruses (BYDV-PAV and BYDV-MAV), cereal yellow dwarf polerovirus (CYDV-RPV), barley stripe mosaic hordeivirus (BSMV), wheat dwarf monogeminivirus (WDV) and brom mosaic bromovirus (BMV) was carried out during May 2003 covering seven cereal-growing counties of Tekirdag, Turkey. Two hundred sixty (260) wheat samples with yellowing, stunting, or striping were collected from 26 wheat fields. These samples were tested for the presence of six viruses by ELISA using polyclonal antisera. Serological tests showed that six tested viruses were present in Tekirdag, Turkey. Among the tested viruses, BYDV-MAV was the most commonly detected (25% of the 260 wheat samples), followed by BYDV-PAV (22.3%), WDV (16.5%), CYDV-RPV (8.5%), BMV (3.1%) and BSMV (1.5%). This study revealed the presence of six viruses in wheat fields in Tekirdag and reported for the first time BSMV and BMV on wheat in Turkey.